Plasmid- and chromosome-coded aerobactin synthesis in enteric bacteria: insertion sequences flank operon in plasmid-mediated systems. - McDougall, S (1984)
Large plasmids were detected in two aerobactin-producing enteric bacterial species (Aerobacter aerogenes 62-I, Salmonella arizona SA1, and S. arizona SL5301) and designated pSMN1, pSMN2, and pSMN3, respectively. Other Salmonella spp., namely, S. arizona SL5302, S. arizona SLS, Salmonella austin, and Salmonella memphis, formed aerobactin but contained no detectable large plasmids. S. arizona SL5283 made no aerobactin. A probe consisting of the aerobactin biosynthetic genes cloned on plasmid pABN5 hybridized to a HindIII digest of pSMN1 but not to digests of pSMN2 or pSMN3. A larger probe, the insert of pABN1 containing the complete aerobactin operon, hybridized to four fragments in HindIII digests of the parent plasmid, pColV-K30. A 2.0-kilobase PvuII fragment responsible for this multiple-hybridization pattern was cloned into vector pUC9 to form pSMN30. The latter was mapped and shown to correspond to either IS1 or to a closely related insertion sequence.